THE PANORAMA OF ATHLETICS IN THE "BOLSA-ATLETA" PROGRAM: AN ANALYSIS BETWEEN THE YEARS OF 2011 TO 2013 - Francielly Nascimento Anunciação; Marcelo Moraes e Silva; Ana Paula Cabral Bonin-Maoski; Carla Cristina Tagliari; Jeferson Roberto Rojo; Fernando Marinho Mezzadri (Universidade Estadual do Oeste do Paraná, 2017)
Abstract: This paper aims to understand what are the main impacts of the government program Bolsa Atleta in the modality of athletics. The period of time used in this study delimits the years 2011 to 2013. The choice of this modality was due to the fact that it was the one that obtained more athletes benefited in the history of the program. The sources used in this research were obtained from lists of athletes included in the program, available on the website of the Ministry of Sport, and the data issued by the Comptroller General of the Union on the program. The variables used were: modalities, level of grant, gender, and geographic distribution of the athletes. The main conclusions of this study are the following: the majority of the athletes benefited is in the intermediate performance levels; there is a balance between the genders among athletes contemplated by the program, with slight predominance of males; and that the beneficiaries are located mainly in the Southeast and South, with a significant concentration in the state of So Paulo. Keywords: Public Policies; Athletics; Public Financing.